Hotel Room Rates And It's Influences To Business Decision Making - Ahmad Fauzy, Haji Hashim (2001)
This study was conducted to determine and obtain facts and resolution regarding the influence of hotel room rates on the sustainance of the hotel industry with particular emphasis on hotels in the northern states of Malaysia viz Kedah, Penang Island, Perlis and Langkawi Island. The special emphasis in this study is to see the various methods used in arriving at how room rates are pegged. In this study, hotels are randomly selected ranging from small hotels which bears no 'star' ratings to five star hotels. Questionnaires were distributed to respondents followed by interpretations. The analysis of these inputs were conducted with the SPSS software using mean statistics, standard deviation, t-tests, ANOVA (analysis of variance) and correlation ststistics. The relevance of the results will be based on the significant level. An accepted significant level will be 0.95 or 5% . The result of this study revealed that hotels do not have a common denominator in pegging room rates to the multi-varied range of customers. Further to this, a series of suggestions and recommendations have been put forward as a guideline to the industry. It is hoped that these guidelines will be a norm in the business practice.